The Reconstruction of The Modern Advertising Concept: An Islamic Law Perspective - Burhanuddin Susamto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Islam as a complete religion needs to offer a modern advertising concept to reconstruct the existing advertising concept, which tends to be value-free. It has the potential to hurt the consumer society. The purpose of this study is to reconstruct the concept of modern advertising using the perspective of Islamic law to serve as alternative guidance for more Islamic advertising practices. To achieve this goal, the author uses the methods of normative legal research with the conceptual approach. The results of this research conclude that the Islamic legal concept of advertising requires fulfillment of the elements and requirements of advertising contract (arkÃ¢n wa syurÅ«th al-i’lÃ¢n) to ensure that the advertiser (al-mu'lin), the object advertised (al-mu'lÃ¢n), the advertising media (wasÃ®lah al-i'lÃ¢n) and the recipient of the advertisement (al-mu'lan lahu) do not conflict with Sharia principles. A producer/ seller can deliver advertising on a product either directly or through advertising media. Advertising media can involve humans and/or other supporting facilities such as writing, posters/ pictures, and musical instruments. The contract underlines the advertising agreement between the sponsor and the advertising service provider to give authority with a wage system (wakÃ¢lah bi al-”˜ujrah).Islam sebagai agama paripurna perlu menawarkan konsep periklanan modern untuk merekonstruksi konsep periklanan yang selama ini cendrung bebas nilai sehingga berpotensi menimbulkan dampak negatif bagi masyarakat konsumen. Tujuan penelitian ini adalah untuk merekonstruksi konsep periklanan modern menggunakan perspektif hukum Islam untuk dijadikan sebagai pedoman alternatif praktik periklanan yang lebih islami. Untuk mencapai tujuan tersebut, penulis menggunakan metode penelitian hukum normatif dengan pendekatan konseptual. Dari hasil penelitian dapat disimpulkan bahwa suatu konsel hukum periklanan yang islami mensyaratkan terpenuhinya rukun dan syarat-syarat iklan untuk memastikan agar pengiklan (al-mu’lin), objek yang diiklankan (al-mu’lÄn), media iklan (wasÃ®lah al-i’lÄn) dan penerima iklan (al-mu’lin lahu) tidak bertentangan dengan prinsip-prinsip syariah. Seorang produsen/ penjual dapat menyampaikan iklan suatu produk baik secara langsung atau melalui media periklanan. Penggunaan media iklan dapat melibatkan peran manusia dan/ atau sarana pendukung lainnya seperti tulisan, poster/ gambar, dan instrumen musik. Adapun akad yang mendasari perjanjian periklanan antara sponsor dengan penyedia jasa iklan adalah perjanjian pemberikan kuasa dengan sistem upah (wakÄlah bi al-”˜ujrah). <w:LsdException Locked